THE EFFECT OF INQUIRY LEARNING ON CRITICAL THINKING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS IN SOCIAL SCIENCE SUBJECT - Stiawan, Agung (Universitas Negeri Surabaya, 2020)
This study aims to determine the effect of the inquiry learning model on the critical thinking skills of junior high school students in social studies subjects the theme of the dynamics of population and national development. The method used was Quasi Experimental method with the Pretest-posttest control group design. The learning model applied to the experimental group was the inquiry model, while the control group was the Problem Base Learning. Subjects were students of class VIII A (experiment) and VIII B (control) at State Junior High School of Probolinggo City academic year of 2018/2019. Data were collected using observation technique, and then analyzed statistically using t-Test on the SPSS program. The results on the posttest data demonstrated a significance (and were supported by the descriptive analysis in which the posttest mean score of the experimental group was higher than the control group